Stearoyl-CoA desaturase-1: a novel key player in the mechanisms of cell proliferation, programmed cell death and transformation to cancer - Igal, R. A. (Carcinogenesis (New York), 2010)
As part of a shift toward macromolecule production to support continuous cell proliferation, cancer cells coordinate the activation of lipid biosynthesis and the signaling networks that stimulate this process. A ubiquitous metabolic event in cancer is the constitutive activation of the fatty acid biosynthetic pathway, which produces saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs) to sustain the increasing demand of new membrane phospholipids with appropriate acyl composition. In cancer cells, the tandem activation of the fatty acid biosynthetic enzymes adenosine triphosphate citrate lyase, acetyl-CoA carboxylase (ACC) and fatty acid synthase (FAS) leads to increased synthesis of SFA and their further conversion into MUFA by stearoyl-CoA desaturase (SCD) 1. The roles of adenosine triphosphate citrate lyase, ACC and FAS in the pathogenesis of cancer have been a subject of extensive investigation. However, despite early experimental and epidemiological observations reporting elevated levels of MUFA in cancer cells and tissues, the involvement of SCD1 in the mechanisms of carcinogenesis remains surprisingly understudied. Over the past few years, a more detailed picture of the functional relevance of SCD1 in cell proliferation, survival and transformation to cancer has begun to emerge. The present review addresses the mounting evidence that argues for a key role of SCD1 in the coordination of the intertwined pathways of lipid biosynthesis, energy sensing and the transduction signals that influence mitogenesis and tumorigenesis, as well as the potential value of this enzyme as a target for novel pharmacological approaches in cancer interventions.